Práticas pedagógicas, tecnologia e o trabalho colaborativo: a inclusão no cotidiano escolar - Berger, Leticia Batista Silva (2021)
This study main objective is to compose pedagogical practices, through collaborative work between teachers of regular and special education, aiming at the real inclusion of students with ID in the final years of elementary school. We will bring as theoretical references the studies of Phillipe Meirieu (1998, 2002, 2005, 2006), and Paulo Freire (1987, 1996, 1999), that will help us to understand the importance of practices in school routine, teacher training, and inventiveness in educational actions. In order to think about the possible collaborative practices between the conducting teacher and the special education teacher in the elementary school of final grades, the case study was thought as a methodological path, as it will allow us to listen sensibly to particular phenomenon, allowing us to an extensive and more objectively understanding, what would be impossible through quantitative methodologies. This thesis embraces, as a final product, a website in multilevel, in the Portuguese language, creating a possibility of a inclusive learning process. Also as a way to enable a critical reflection about the importance of collaboration and differentiated educational practices as of students reality. As a result, this study will, hopefully, contribute with collaborative practices with technology support that can serve as a reference to whoever intends to produce educational practices through collaborative work that focuses on students that are the target of special education. Hopefully this research will serve as a reference for others with similar theme, and can be deepened in other contexts.